Extreme Saharan dust outbreak: Air quality crisis in NW Spain (March 2022) - Cátia Gonçalves; Estela D. Vicente; Carlos Blanco-Alegre; Ana Isabel Calvo; Maria del Mar Sorribas; Fabio Giardi; Silvia Nava; Giulia Calzolai; Alberto Rodríguez-Fernández; Carla Candeias; Roberto Fraile (Atmospheric Pollution Research, 2026)

Exposure to pharmaceutical contaminants in stranded wild dolphins of the Western Mediterranean - Isabel Navas; Mar Felipo-Benavent; Jose Luis Crespo-Picazo; Daniel García-Párraga; Alicia Martínez-Romero; Francisco García-García; Jose-Enrique O'Connor; Consuelo Rubio-Guerri; Antonio J. García-Fernández (Science of The Total Environment, 2026)

Metals in feathers of the red-billed chough as a sentinel of exposure to past and recent volcanic activity in La Palma, Canary Islands - Guillermo Blanco; Isabel Navas; Martina Carrete; Pedro María-Mojica; Félix M. Medina; Óscar Frías; José L. González del Barrio; Sara Gutiérrez; Raymundo Montoya Ayala; Antonio J. García-Fernández (Environmental Research, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Neuroprotective effect of copper on neurotoxicity of TOCP in vivo - Brenda Rosales-Castro; Isabel Bravo-Ontiveros; Keyla Betanzos-Rau; Kenia Nava-Aparicio; Laura Ramírez-González; Elizabeth Undiano; Iván Flores-Pérez; Eugenio Vilanova; Antonio Monroy-Noyola (Chemico-Biological Interactions, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Marine Prosperity Areas: a framework for aligning ecological restoration and human well-being using area-based protections - Octavio Aburto-Oropeza; Valentina Platzgummer; Erica M. Ferrer; Catalina López-Sagástegui; Rocío de Guadalupe Abud Mirabent; América Ávalos Galindo; Fabio Favoretto; Alfredo Giron-Nava; Isabel Mendoza Camacho; Claudia Núñez Sañudo; Marisol Plascencia de La Cruz; Alejandro Robles (Frontiers in Marine Science, 2025)
Mechanisms for marine ecological protection and recovery, including area-based conservation tools like ‘Marine Protected Areas’ (MPAs) are necessary tools to reach the Aichi Target or the forthcoming 30x30 target set by the Kunming-Montreal Biodiversity Framework. However, full ecosystem recovery takes years to manifest and the idea that MPA protection alone will foster human well-being is frequently contradicted by socio-economic evidence. Therefore, a new framework for marine area-based conservation and ecosystem restoration that reconciles the discrepancies between ecological recovery and socio-economic growth timelines is needed to effectively meet global biodiversity conservation targets. We introduce the concept of ‘Marine Prosperity Areas,’ (MPpA) an area-based conservation tool that prioritizes human prosperity as opposed to passively relying on ecosystem recovery to catalyze social change and economic growth. This concept leverages a suite of tried-and-true community-based intervention and investment strategies to strengthen and expand access to environmental science, social goods and services, and the financial perks of the blue economy. This data-driven framework may be of interest to stakeholders who support traditional area-based conservation models, but also to those who have been historically opposed to MPAs or have been excluded from past conservation processes.

Behavioral and physiological changes of Anisakis simplex complex third stage larvae upon heating - Aiyan Guan; Marina Usieto; Laura Otero; Susana C. Arcos; Alfonso Navas; Isabel Sánchez-Alonso; Mercedes Careche (Food Control, 2024)

Age and sex differences in pharmaceutical contamination in a keystone scavenger - Guillermo Blanco; Martina Carrete; Isabel Navas; Antonio J. García-Fernández (Environmental Research, 2024)

Greater predisposition to second generation anticoagulant rodenticide exposure in red foxes (Vulpes vulpes) weakened by suspected infectious disease - Alberto Carrera; Isabel Navas; Pedro María-Mojica; Antonio J. García-Fernández (Science of The Total Environment, 2024)

Trophic status of a coastal lagoon - marine harbor system: Potential outwelling rates to the Mesoamerican Barrier Reef southern region - Juan Carlos Carrasco Navas-Parejo; Sokratis Papaspyrou; Sara Haro; Isabel Caballero de Frutos; Alfonso Corzo (Science of The Total Environment, 2023)

Deforestation and trends of change in protected areas of the Usumacinta River basin (2000–2018), Mexico and Guatemala - José Alberto Gallardo-Cruz; Candelario Peralta-Carreta; Jonathan Vidal Solórzano; Ana Isabel Fernández-Montes de Oca; Luzma Fabiola Nava; Edith Kauffer; Julia Carabias (Regional Environmental Change, 2021)

Wildlife poisoning: a novel scoring system and review of analytical methods for anticoagulant rodenticide determination - Irene Valverde; Silvia Espín; Pilar Gómez-Ramírez; Isabel Navas; Pedro María-Mojica; Pablo Sánchez-Virosta; Pedro Jiménez; María Y. Torres-Chaparro; Antonio J. García-Fernández (Ecotoxicology, 2021)

Mercury Exposure in Birds Linked to Marine Ecosystems in the Western Mediterranean - Silvia Albertos; Neus I. Berenguer; Pablo Sánchez-Virosta; Pilar Gómez-Ramírez; Pedro Jiménez; María Y. Torres-Chaparro; Irene Valverde; Isabel Navas; Pedro María-Mojica; Antonio J. García-Fernández; Silvia Espín (Archives of Environmental Contamination and Toxicology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Mercury and Organochlorine Pesticides in Tissues of Loggerhead Sea Turtles (Caretta caretta) Stranded Along the Southwestern Mediterranean Coastline (Andalusia, Spain) - Pilar Gómez-Ramírez; Silvia Espín; Isabel Navas; Emma Martínez-López; Pedro Jiménez; Pedro María-Mojica; José Peñalver; Antonio J. García-Fernández (Bulletin of Environmental Contamination and Toxicology, 2020)

Conditioned food aversion mediated by odour cue and microencapsulated levamisole to avoid predation by canids - Jorge Tobajas; Pilar Gómez-Ramírez; Pedro María-Mojica; Isabel Navas; Antonio Juan García-Fernández; Pablo Ferreras; Rafael Mateo (European Journal of Wildlife Research, 2019)

The influence of dietary fat source on liver and skeletal muscle mitochondrial modifications and lifespan changes in calorie-restricted mice - José Manuel Villalba; José Alberto López-Domínguez; Yana Chen; Husam Khraiwesh; José Antonio González-Reyes; Lucía Fernández del Río; Elena Gutiérrez-Casado; Mercedes del Río; Miguel Calvo-Rubio; Julia Ariza; Rafael de Cabo; Guillermo López-Lluch; et al. (Biogerontology, 2015)

Potato, an experimental and natural host of the crinivirus Tomato chlorosis virus - Isabel M. Fortes; Jesús Navas-Castillo (European Journal of Plant Pathology, 2012)

Physalis ixocarpa and P. peruviana, new natural hosts of Tomato chlorosis virus - Helena P. Trenado; Isabel M. Fortes; Diamantina Louro; Jesús Navas-Castillo (European Journal of Plant Pathology, 2007)